SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TELADAN DI SEKOLAH DASAR NEGERI 3 PUJODADI PRINGSEWU MENGGUNAKAN METODE TOPSIS - Idris, Muhammad; Susanto, Feri (YHMM PUBLISHING, 2024)
The selection of exemplary teachers is one form of appreciation and motivation for educators who demonstrate outstanding performance. However, the selection process is often not based on a structured and objective system, which may lead to inaccuracies in decision-making. This study aims to develop a Decision Support System (DSS) to assist the selection process of exemplary teachers at SD Negeri 3 Pujodadi Pringsewu using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method is chosen because it provides a ranking of alternatives based on their proximity to the ideal positive and negative solutions. In this study, five criteria are used for the assessment: Performance Certificates, Educational Background, Work Discipline, Work Quality, and Years of Service. Each teacher, as an alternative, is evaluated based on the weight and score of each criterion, which is then processed through the TOPSIS stages including normalization of the matrix, weighting, determining the positive and negative ideal solutions, and calculating distances and preference values. The result of this system provides an objective and measurable recommendation for selecting exemplary teachers. With the implementation of a TOPSIS-based DSS, the selection process is expected to become more transparent, accurate, and accountable. This system may also serve as a reference for other schools in developing multi-criteria-based evaluation systems.